2016
DOI: 10.5433/1679-0359.2016v37n3p1135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, classification and analysis of the main properties of the Southwestern Goias soil

Abstract: Characterization of the soil and the grouping of its properties through main component analysis can assist in the classification and observation of the consequences of the conversion of native forest areas in pastures. Such data can aid in management practices. Considering the lack of studies in Cerrado soils of south-western Goias, developed metagranites of Jurubatuba suite, the objective was to classify and study the physical, chemical and mineralogical soil (under native forest and pasture) Southwest of Goi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…This natural condition expresses the organic matter input that is deposited in this environment. Gomes et al (2004) and Fernandes et al (2016) found this same distribution pattern in an area under forest and "Cerrados" environments, indicating the great nutrient cycling capacity and favoring natural fertility maintenance in superficial horizons.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 71%
“…This natural condition expresses the organic matter input that is deposited in this environment. Gomes et al (2004) and Fernandes et al (2016) found this same distribution pattern in an area under forest and "Cerrados" environments, indicating the great nutrient cycling capacity and favoring natural fertility maintenance in superficial horizons.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 71%
“…The climate type of the region, according to Köppen's classification, is tropical wet (Aw), with dry winters and rainy summers (Ribeiro & Walter, 2008). The source material from the site is composed of metamorphic metagranites of the Jurubatuba formation from the Proterozoic age, as characterized by Fernandes et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Para Correa et al (2008a) a gênese dos horizontes coesos em solos dos Tabuleiros Costeiros é derivada do translocação de argila fina de composição caulinítica. O maior adensamento desses horizontes estariam então relacionados aos ajuste face a face dessas caulinititas (LIMA NETO et al, 2010;FERNANDES et al, 2016).…”
Section: Mineralogiaunclassified